2021
DOI: 10.3389/fbioe.2021.718996
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Different Surgical Approaches for the Treatment of Adjacent Segment Diseases After Primary Anterior Cervical Discectomy and Fusion: A Finite Element Analysis

Abstract: Symptomatic adjacent segment disease (ASD) is a common challenge after anterior cervical discectomy and fusion (ACDF). The objective of this study was to compare the biomechanical effects of a second ACDF and laminoplasty for the treatment of ASD after primary ACDF. We developed a finite element (FE) model of the C2-T1 based on computed tomography images. The FE models of revision surgeries of ACDF and laminoplasty were simulated to treat one-level and two-level ASD after primary ACDF. The range of motion (ROM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
1
6
0
1
Order By: Relevance
“…The results showed that the ROMs of the surgical segments in all movement directions decreased by 85.9%–91.6% postoperatively, which is consistent with the outcomes of previous literature ( Hua et al, 2020b ; Ke et al, 2021 ). Attributed to the anterior fixation and interbody fusion, sacrificed ROM at the fused segments mainly indicated strong immobilization ( Gao et al, 2012 ; Song and Choi, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that the ROMs of the surgical segments in all movement directions decreased by 85.9%–91.6% postoperatively, which is consistent with the outcomes of previous literature ( Hua et al, 2020b ; Ke et al, 2021 ). Attributed to the anterior fixation and interbody fusion, sacrificed ROM at the fused segments mainly indicated strong immobilization ( Gao et al, 2012 ; Song and Choi, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…The increased mobility of the unfused segment when compared to that of the normal group might be due to the loss of fusion of the fused segments and the compensation of the preserved normal cervical mobility. ACDF was of sacrificed ROM at the fused segments, while increased stress in the adjacent segment may be an important cause for developing adjacent segment degeneration (ASD) ( Eck et al, 2002 ; Hua et al, 2020a ; Ke et al, 2021 ). Considering that the ROM in the assembled uncovertebral joint fusion cage model achieved similar results to those after implantation with the Zero-P device, it is prudent to speculate that the assembled uncovertebral joint fusion cage did not significantly accelerate the degeneration of adjacent segments when compared with Zero-P.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that both the methods can provide beneficial short-term effects [ 26 , 27 ]. On the contrary, spinal fusion is performed for coping with lumbar instability in the PLIF procedure, which can be attributed to some complications such as adjacent segment diseases (ASD) [ 5 , 6 , 28 ], considering that the spinal fusion may change the rotation center over the disc, increasing the stress on the intervertebral disc of the adjacent mobile segments [ 29 ]. We also noted improvements in the VAS score and ODI at the last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The STL file was imported into SolidWorks 2017 computer-aided design software (Dassault Systèmes SolidWorks Corporation, Waltham, Massachusetts, USA). The cortical bone, cancellous bone, endplate, annulus fibrosus, nucleus pulposus, articular cartilage, and other elements were created based on previous literature [ 20 ]. An cervical spine model of C2-C7 was created with all the elements mentioned above.…”
Section: Methodsmentioning
confidence: 99%